Combination of a Novel Genetic Variant in CFB Gene and a Pathogenic Variant in COL4A5 Gene in a Sibling Renal Disease: A Case Report - Wang, Feng-mei; Yang, Yan; Zhang, Xiao-liang; Wang, Yan-li; Tu, Yan; Liu, Bi-Cheng; Wang, Bin (Frontiers in Genetics, 2021)
Complement factor B mutations have been described to play a causative role in auto-immune associated C3 glomerulopathy and/or atypical hemolytic uremic syndrome (aHUS) by affecting the dysregulations of alternative pathway activation. However, CFB mutation concomitant with COL4A5 mutation is scarce. Here, we depict two intriguing cases with concurrent novel heterozygosity for CFB c.2054_2057del(S687Pfs*16) and a previous reported COL4A5 p.G1000V (c.2999G>T) mutation in a pair of siblings. The clinical feature of either paternal CFB mutation or maternal COL4A5 mutation is just mild microscopic hematuria. Interestingly, their two children with paternal CFB c.2054_2057del(S687Pfs*16) mutation and maternal COL4A5 p.G1000V (c.2999G>T) mutation simultaneously presented with massive proteinuria, hematuria, progressive renal failure with poor treatment response. Moreover, complement pathway activation in renal tissue further supports and strengthens the pathogenic role of CFB mutation in the development of renal injury on the basis of COL4A5 mutation. In conclusions, the rare sibling cases highlight that genetic diagnosis in families is helpful for the diagnosis and understanding of some family cluster renal diseases.